Pemanfaatan Limbah Rumah Tangga Menjadi Ekoenzim Di Desa Kandangmas, Kabupaten Kudus - Nova Laili Wisuda (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Kandangmas Village through the PKK mobilization team conducts a household waste treatment program one of which is by processing it into eco-enzymes. The stages of this program start from surveys and program planning, introduction of mentoring through workshops and training, monitoring evaluation, review of service results, and final report of service. The results of the household waste treatment program as many as 40% stated that this program is beneficial and 32% stated that it is quite important to be useful. Eco-enzyme products have an aroma favored by partners and are used for various purposes, in particular for anti-septic agents and plant nutrient additives.